Fault detection of Discrete-Event Systems based on an identified timed model. (December 2020) - de Souza, Ryan P.C.; Moreira, Marcos V.; Lesage, Jean-Jacques
Abstract: In this paper, a method for fault detection of Discrete-Event Systems (DES) based on a timed model called Timed Automaton with Outputs and Conditional Transitions (TAOCT), obtained by identification, is presented. The TAOCT is an extension of a recent untimed model proposed in the literature, called Deterministic Automaton with Outputs and Conditional Transitions (DAOCT). Differently from the DAOCT, where only the logical behavior of the DES is considered, the TAOCT takes into account information about the time that the events are observed, and, for this reason, it can be used for the detection of faults that cannot be detected by using untimed models, such as faults that lead the fault detector to deadlocks. The TAOCT represents the fault-free system behavior, and a fault is detected when the observed behavior is different from the one predicted by the model, considering both logical and timing information. A practical example is used to illustrate the results of the paper.